Investments in “smallholder” family farming. Towards a New Deal - Bosc, Pierre-Marie (Perspective, 2015)
<span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value=""1":2,"2":"Investment in agriculture has declined since the 1980s, and public policies are needed to ensure smallholder farmers are able to invest in their farms. The priority objective is to create a secure, enabling environment so that these farmers can free up the necessary resources, in terms of both time and money. These policies span several different sectors and must therefore be integrated. This is the condition on which smallholder family farmers will be able to reach their full potential in contributing to food and nutrition security, job creation, the reduction of poverty and inequality, and territorial development."" data-sheets-userformat=""2":577,"3":[null,0],"9":0,"12":0">Version française de l'article <span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value=""1":2,"2":"Investment in agriculture has declined since the 1980s, and public policies are needed to ensure smallholder farmers are able to invest in their farms. The priority objective is to create a secure, enabling environment so that these farmers can free up the necessary resources, in terms of both time and money. These policies span several different sectors and must therefore be integrated. This is the condition on which smallholder family farmers will be able to reach their full potential in contributing to food and nutrition security, job creation, the reduction of poverty and inequality, and territorial development."" data-sheets-userformat=""2":577,"3":[null,0],"9":0,"12":0">Versión en español del artículo <span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value=""1":2,"2":"Investment in agriculture has declined since the 1980s, and public policies are needed to ensure smallholder farmers are able to invest in their farms. The priority objective is to create a secure, enabling environment so that these farmers can free up the necessary resources, in terms of both time and money. These policies span several different sectors and must therefore be integrated. This is the condition on which smallholder family farmers will be able to reach their full potential in contributing to food and nutrition security, job creation, the reduction of poverty and inequality, and territorial development."" data-sheets-userformat=""2":577,"3":[null,0],"9":0,"12":0">Investment in agriculture has declined since the 1980s, and public policies are needed to ensure smallholder farmers are able to invest in their farms. The priority objective is to create a secure, enabling environment so that these farmers can free up the necessary resources, in terms of both time and money. These policies span several different sectors and must therefore be integrated. This is the condition on which smallholder family farmers will be able to reach their full potential in contributing to food and nutrition security, job creation, the reduction of poverty and inequality, and territorial development.